The impact of mental accounting on tax evasion (an experimental study in accounting students) - Aprilia Kardianzah Putri; Tarjo Tarjo; Achdiar Redy Setiawan (STIE Perbanas Surabaya, 2018)
The purpose of this study is to fi nd out the impact of mental accounting on tax evasion decisions. This research is a quantitative research using experimental research methods. Analysis was conducted using 2x3 between subjects experimental design. The sample used in this experiment was accounting students at Trunojoyo University, Madura, with concentration on taxation. The results for all treatments in this study indicate that there are no differences between in gain scenario and loss scenario. These fi ndings can be explained by mental accounting and prospect theory. This study shows that individuals evaluate tax payments and tax refunds asymmetrically. In addition, the individuals also underlie mental accounting when making tax evasion decisions.